Long and winding roads the evolving artistry of the Beatles - Womack, Kenneth (New York, NY, USA Bloomsbury Academic, 2023)
"A follow-up to the successful 2007 edition, which, despite numerous Beatles-related books published in the intervening years, still stands alone for its chronological, album-by-album analysis of the band's work"--Provided by publisher.
Prologue : The End -- The Beginning -- A Cellarful of Noise -- And the Band Begins to Play -- Rock and Roll Music -- The Biggest Showbiz Town Ever -- War-Weary -- Yesterday and Today -- Plastic Soul -- The End of the Road -- The Act You've Known for All These Years -- Roll Up for the Mystery Tour -- Whiter Shades of Pale -- Getting Back -- The Dream Is Over -- Epilogue : Long Live the Dream.
Includes bibliographical references and index.
Keywords: Beatles; Rock music -- Analysis, appreciation; Rock musicians -- England